Analysis of Physical Demands During Youth Soccer Match-Play: Considerations of Sampling Method and Epoch Length. Issue 2 (2nd April 2020) - Doncaster, Greg; Page, Richard; White, Paul; Svenson, Robert; Twist, Craig
ABSTRACT: Purpose: The purpose of this study was to examine the physical match profiles of professional soccer players using 3 and 5 min fixed and rolling averages as well as fixed 1 min averages, with considerations to training prescription. Methods: Twenty-nine professional U23 soccer outfield players competed across 17 competitive matches during the 2017/18 season, equating to a total of 130 separate physical match profiles. Match activities were recorded using global positioning system (GPS) devices with integrated micro-electrical mechanical systems (MEMS), recording total distance (TD), high-speed running (HSR), and metabolic power (MP). For each individual match profile and variable, 1, 3, and 5 min peak, post-peak, and average values were calculated using fixed-time epochs (FIXED) and rolling averages (ROLL). Linear mixed models were employed to examine the differences in the dependent variables as a function of the method of measurement. Results: Results revealed significantly higher peak values, for relative TD, relative HSR and relative MP when employing the ROLL sampling method, in comparison to the FIXED method, for both 3 min and 5 min epoch lengths. Analysis of epoch length revealed significantly higher peak values, across all positions, for relative TD, relative HSR and MP for 1 min epochs, in comparison to 3 min and 5 min epochs. Conclusions: The data offers a novel insight into the appropriate identification of physical demands during youth soccer match-play. Researchers and practitioners should consider the sampling method and epoch length when assessing the physical demands of competitive match-play, as well as when designing and prescribing sport-specific conditioning drills.